THE INTELLIGENTSIA : IT S CONCEPT , DEVELOPM ENT AND ED UCATI ON IN CONCEPTI ON OF STASYS ŠALKAUSKIS - Šalkauskas, Julius (Acta Paedagogica Vilnensia, 2008)
The concepts of intellectuals and intelligentsia were defined and analysed in terms of educational ideas of Stasys Šalkauskis. Such analysis is actual because named concepts often are confused. In contemporary literature „inteligentas“ and „intelektualas“ are considered as identical concepts.After definitions and analysis by S. Šalkauskis of those concepts were prooved that they are essentially different acordingly to the difference between concepts of an inteligent person and an intelectual person. Although in English both concepts are named with the same word „intellectual“.The community of intellectuals which satisfy the criterions of intelligentsia defined by S. Šalkauskis compose intelligentsia which have a dominant and positive role in cultural and social processes in society, nation and state.The role of intelligentsia in Lithuania in different periods of lithuanian history were viewed. It is shown that intelligents and intllectuals are not in consolidation but rather are divided in different groups which are of different world oulook and often are in state of mutual noncomunication and involved in severe conflicts.The result of such a situation is social, cultural and political chaos which create danger for identity of Lithuanian nation its culture and independence of the Lithuanian state. The progress in this unhappy situation is possible only if the new young positive and active intelligentsia in accordance with the concept of Šalkauskis can be created.
Keywords: intellectual; intelligentsia; intellectuals in Lithuania; influence and education of intellectuals and intelligentsia